Reflective Practice in ESL Teacher Development Groups From Practices to Principles - Farrell, Thomas S. C.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Reflective Practise in ESL Teacher Development Groups discusses the concept of reflective practice in ESL teachers using data from a 3-year collaborative partnership in which three ESL teachers in Canada explored their professional development through reflective practice.
Keywords: Education; Linguistics; Applied linguistics; Language and education; Teaching; Language and languages -- Study and teaching; Education; Teaching and Teacher Education; Language Teaching; Linguistics, general; Applied Linguistics; Language Education